Methodology for the synthesis of environmentally compliant chemical process system, case study: the production of biodiesel from vegetable oils - Retno Gumilang Dewi (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2004)
Among of the basic processes in a chemical process system, chemical reaction is the first stage and is considered as the most important step of a chemical process design undertaking as it determines the design of subsequent processes. Thereby, the design of 'environmentally compliant' chemical process system hinges on how the chemical reaction is synthesized and environmental consideration is integrated into the design processes of chemical process system that is minimal in the generation of spent resources, efficient in the use of raw materials, and prioritize the use of renewable resources. An attempt was carried out to formulate a methodology by which a preliminary screening can be made to come up with a set of chemical reaction paths. Based on these selected reaction paths, the optimization process is then carried out to maximize the economic performance of the. reaction system using environmental compliances as optimization constraint. The optimal reaction path will lead to the formulation of various species allocation schemes in the reaction system. Most feasible reaction paths are screened from species allocation alternative schemes. The best scheme is selected based on some parameters, namely (i) the efficiency of raw material utilization per unit product, (ii) economic potential regarding the gross profit margin, and (iii) environmental aspects concerning the pollution potential from the production system. A computer program 'Hysis' is used in this study to evaluate these parameters.Key Words : Reaction Path Synthesis, Renewable-based Processes, Environmentally Compliant, Chemical Process DesignAbstrakDi antara proses-proses dasar dalam suatu sistem proses kimia,proses reaksi kimia merupakan tahap utama yang paling penting dan menjadi penentu di dalam perancangan proses kimia. Dengan demikian, perancangan sistem proses kimia yang 'memenuhi persyaratan lingkungan' tergantung bagaimana proses reaksi kimia disintesakan dan pertimbangan lingkungan diintegrasikan ke dalam perancangan sistem yang minimal dalam pembentukan limbah, efisien dalam penggunaan bahan baku, dan mengutamakan penggunaan sumber daya yang terbarukan. Suatu upaya telah dilakukan untuk memformulasikan sebuah metodologi di mana penseleksian awal dapat dibuat untuk memunculkan satu kelompok rute-rute reaksi. Berdasarkan rute-rute reaksi ini, optimisasi dilakukan untuk memaksimalkan potensi ekonomi dari sistem proses kimia yang dibentuk berdasarkan rute-rute reaksi yang dipilih pada penseleksian awal dengan menggunakan pemenuhan persyaratan lingkungan sebagai batasan-batasan yang digunakan dalam pelaksanaan optimisasi. Rute reaksi yang optimal ini akan berperan di dalam pembentukan berbagai macam pola pengalokasian komponen bahan ('species allocation'). Pola pengalokasian komponen bahan yang terbaik, dipilih berdasarkan sekumpulan parameter yang terdiri ataspertimbangan-pertimbangan teknis, ekonomis, dan lingkungan. Program 'Hysis' digunakan pada penelitian ini untuk mengevaluasi parameter parameter tersebut.Kata Kunci : Sintesa Rute Reaksi, Proses-proses Terbarukan, Memenuhi Persyaratan Lingkungan, Desain Proses Kimia